The Implementation of the Jigsaw Learning Model to Improve Students Learning Outcomes in the Subject of Akidah Akhlak for Grade VI at MI PSM Gedoro Ngawi - Ratna Utami Nur Ajizah; Saiful Anwar; Anggun Saskiya; Dewi Nur Alipah; Miftahul Halima (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
With the development of science and technology, education in Indonesia continues to progress, and globalization is advancing. The goals of education cannot be achieved without a learning process within an educational institution. To attain perfect learning objectives, teachers need to innovate in their teaching methods. Jigsaw is a structured group work strategy based on cooperation and responsibility. In this research, the researcher employed the Classroom Action Research (CAR) method. This strategy is appealing when the material to be studied can be divided into several parts and does not require a specific sequence of delivery. Based on the results and discussion of the research, the researcher concludes that the use of the jigsaw learning model is capable of improving the learning outcomes of sixth-grade students in the subject of Akidah Akhlak at MI PSM Gedoro Ngawi.